Peran Content Creator sebagai Agen Bela Negara dalam Menangkal Disinformasi: Studi Kasus Konten Ferry Irwandi - Fadia Az-Zahra Puteri; Monica Biyant Balqis; Dimas Setiawan; Maia Safira Choirunnisa; Inggrid Manusatun Nadia; Sultan Falih Rheinsalazar (CV. Denasya Smart Publisher, 2025)
Disinformation is one of the real threats to national stability in the digital era that needs to be addressed immediately. This study aims to analyze the role of content creators in countering disinformation in the digital era, focusing on Ferry Irwandi's content on social media. The method used is descriptive qualitative research with secondary data collection through content analysis of ten Ferry Irwandi videos. The results show that several of Ferry Irwandi’s contents feature five main thematic indicators: counter-narratives against disinformation, strengthening the narrative of national defense, digital and media literacy education, issues of tolerance and diversity, and social criticism based on national values. These findings demonstrate that defending the nation can be realized through creative, critical, and educational content, which becomes one of the key strategies in addressing the threat of disinformation in the digital space.